CULTURAL ADAPTATION STRATEGIES OF THE TORAJA ETHNIC GROUP IN SOCIAL INTERACTION AT LONG BELEH HALOQ VILLAGE, KEMBANG JANGGUT DISTRICT, KUTAI KARTANEGARA REGENCY - Adeliah Dwy Arianti; Jawatir Pardosi; Aloysius Hardoko; M Jamil (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to identify the social structure of the Toraja ethnic community in Long Beleh Haloq Village, describe cultural adaptation strategies in social interactions within a multiethnic environment, and examine supporting and inhibiting factors affecting adaptation. The study employed a qualitative descriptive method with a case study approach. Data were collected through observation, in-depth interviews, and documentation using purposive sampling. Eleven informants participated, consisting of members of the Toraja Family Association (IKAT), Toraja residents, local villagers, and the village head. The research was conducted from February to May 2025. Data analysis followed stages of data collection, reduction, display, and conclusion drawing, while validity was ensured through source and method triangulation. Findings show that the social structure of the Toraja community in Long Beleh Haloq Village is egalitarian and functional, where social status is determined by contribution, responsibility, and social roles rather than lineage. Cultural adaptation strategies include contextual language use, participation in work and communal activities, preservation of the traditional wedding ceremony Rampanan Kapa’, and active roles of families and IKAT in maintaining values of mutual cooperation, solidarity, tolerance, and togetherness. Supporting factors consist of strong internal cohesion, openness, and acceptance from local communities. Inhibiting factors involve differences in customs, coordination constraints, and geographical distance between settlements. Overall, the Toraja community is able to maintain cultural identity while adapting harmoniously to a new social environment through mutual respect and intercultural cooperation within an increasingly diverse rural Indonesian social context.